HUBUNGAN USIA DENGAN KEJADIAN SPOTTING PADA AKSEPTOR KB IMPLAN DI PUSKESMAS GRABAG, PURWOREJO: Association Between Age and Spotting Among Contraceptive Implant Acceptors at Grabag Community Health Center, Purworejo - Ulfah Hidayati; Nur Sholichah (Jurnal Komunikasi Kesehatan, 2026)
Spotting is light bleeding that occurs outside the menstrual cycle. Spotting is often associated with hormonal disturbances caused by the use of hormonal contraceptives, one of which is the implant. A preliminary study showed that 2 out of 10 implant acceptors experienced spotting. This study aimed to determine the relationship between age and the incidence of spotting among implant family planning acceptors at Grabag Public Health Center, Purworejo. This research was a quantitative study with a cross-sectional design using a retrospective approach. A total of 90 respondents were selected using total sampling. Data collection was conducted from January to July 2025. Data were analyzed using univariate and bivariate analysis. Bivariate analysis was performed using the chi-square test to assess the relationship between age and the incidence of spotting among implant family planning acceptors. The results showed a p-value of 0.06 (p > 0.05), indicating that there was no relationship between age and the incidence of spotting among implant family planning acceptors at Grabag Public Health Center, Purworejo.